Contrasting thermosolvatochromic trends in pyridinium-, pyrrolidinium-, and phosphonium-based ionic liquids - Khupse, Nageshwar D.; Kumar, Anil (Journal of Physical Chemistry B, 2010)
Thermosolvatochromism has been studied in three series of ionic liquids, pyridinium-based 1-butylpyridinium, 1-hexylpyridinium, and 1-octylpyridinium with bis(trifluoromethylsulfonyl)imide [NTf2] and tetrafluoroborate [BF4] anions, pyrrolidinium-based ionic liquids 1-methyl-1-butylpyrrolidium, 1-methyl-1-hexylpyrrolidium, 1-methyl-1-octylpyrrolidium with bis(trifluoromethylsulfonyl) imide anion and phosphonium-based ionic liquids tetrabutylphosphonium with alanate and valinate anions. The effect of increase in alkyl chain length and temperature on normalized polarity E-T(N), Kanilet-Taft parameters, hydrogen bond donor ability (alpha), hydrogen bond acceptor ability (beta), and polarizability (pi*) was investigated in the temperature range of 298-353 K. Interestingly, the polarity decreases with temperature in the case of pyridinium- and pyrrolidinium-based ionic liquids, and it increases with temperature in the case of phosphonium-based ionic liquids.

Cosolvent-directed diels-alder reaction in ionic liquids - Khupse, Nageshwar D.; Kumar, Anil (Journal of Physical Chemistry A, 2011)
The rate constants of a bimolecular Diels-Alder reaction in binary mixtures of ionic liquids prepared in molecular solvents were analyzed to investigate the effect of viscosity of the medium and solvent effect. In this connection, we have carried out the Diels-Alder reaction of anthracene 9-carbinol with N-ethyl maleimide in binary mixtures of pyridinium-based ionic liquids, 1-butyl-pyridinium tetrafluoroborate, 1-buty1-3-pyridinium tetrafluoroborate, and 1-butyl-4-methyl pyridinium tetrafluoroborate in water, methanol, and chloroform at 298.15 K. The rates of reaction decreased, caused by gradually increasing the volume fraction of ionic liquids in solvents for all three ionic liquids. The kinetic results demonstrate a successful application of the pairwise interaction model built upon the concept of enforced hydrophobic hydration. A temperature-dependent study of kinetics of the Diels-Alder reaction was carried out in the binary mixtures of ionic liquids in water and was explained by the entropy-enthalpy compensation effect based upon activation parameters. Kinetics of the Diels-Alder reaction in highly aqueous medium was noted to be entropically driven.

Comparative investigation of the ionicity of aprotic and protic ionic liquids in molecular solvents by using conductometry and NMR spectroscopy - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Chemphyschem, 2016)
Electrical conductivity (sigma), viscosity (), and self-diffusion coefficient (D) measurements of binary mixtures of aprotic and protic imidazolium-based ionic liquids with water, dimethyl sulfoxide, and ethylene glycol were measured from 293.15 to 323.15K. The temperature dependence study reveals typical Arrhenius behavior. The ionicities of aprotic ionic liquids were observed to be higher than those of protic ionic liquids in these solvents. The aprotic ionic liquid, 1-butyl-3-methylimidazolium tetrafluoroborate, [bmIm][BF4], displays 100% ionicity in both water and ethylene glycol. The protic ionic liquids in both water and ethylene glycol are classed as good ionic candidates, whereas in DMSO they are classed as having a poor ionic nature. The solvation dynamics of the ionic species of the ionic liquids are illustrated on the basis of the (HNMR)-H-1 chemical shifts of the ionic liquids. The self-diffusion coefficients D of the cation and anion of [HmIm][CH3COO] in D2O and in [D-6]DMSO are determined by using H-1 nuclei with pulsed field gradient spin-echo NMR spectroscopy.
Keywords: conducting materials; Electrochemistry; electrostatic interactions; Ion pairs; ionic liquids